Repetition Suppression in Visual and Auditory Modalities Affects the Sound-Induced Flash Illusion. (June 2021) - Wang, Aijun; Zhou, Heng; Yu, Wei; Zhang, Fan; Sang, Hanbin; Tang, Xiaoyu; Zhang, Tianyang; Zhang, Ming
Sound-induced flash illusion (SiFI) refers to the illusion that the number of visual flashes is equal to the number of auditory sounds when the visual flashes are accompanied by an unequal number of auditory sounds presented within 100 ms. The effect of repetition suppression (RS), an adaptive effect caused by stimulus repetition, upon the SiFI has not been investigated. Based on the classic SiFI paradigm, the present study investigated whether RS would affect the SiFI differently by adding preceding stimuli in visual and auditory modalities prior to the appearance of audiovisual stimuli. The results showed the auditory RS effect on the SiFI varied with the number of preceding auditory stimuli. The hit rate was higher with two preceding auditory stimuli than one preceding auditory stimulus in fission illusion, but it did not affect the size of the fusion illusion. However, the visual RS had no effect on the size of the fission and fusion illusions. The present study suggested that RS could affect the SiFI, indicating that the RS effect in different modalities would differentially affect the magnitude of the SiFI. In the process of multisensory integration, the visual and auditory modalities had asymmetrical RS effects.